Early warning and response systems for respiratory disease outbreaks: lessons learnt from cluster-associated cases of acute respiratory illnesses in Gilgil subcounty, Nakuru County, Kenya, 2021 - Linus Ndegwa; Philip Ngere; Lyndah Makayotto; Eric Osoro; Elizabeth Kiptoo; Peninah Munyua; Amy Herman-Roloff; Radhika Gharpure; M Kariuki Njenga; Stella Mamuti; Erenius Lochede Nakadio; Rosalia Kalani; et al. (BMJ Global Health)
Investigating acute respiratory illnesses (ARIs) is difficult due to non-specific symptoms, varied health-seeking behaviors, and resource limitations; yet early detection is critical to global health security. Kenya's Ministry of Health (MOH) uses the Integrated Disease Surveillance strategy for public health surveillance, incorporating event-based surveillance (EBS) and indicator-based surveillance (IBS) for early warning system. MOH, supported by the US-CDC, established Influenza Sentinel Surveillance (ISS) in 2006 and later launched community EBS (CEBS) and health facility EBS (HEBS) pilots to enhance surveillance for COVID-19. On March 2, 2021, the CEBS system detected a signal of “Two or more people presenting with similar signs and symptoms in a community within a week” in a county. Investigations launched on March 4, 2021, investigations revealed unreported ARI cases which had been missed by both the ISS and IBS. A total of 176 ARI cases were line-listed with 91/176 (51.7%) aged <5-years and 46/176 (26.1%) hospitalized. RT-PCR tests confirmed 34/79 (43.0%) SARS-CoV-2 and 1/7 (14.3%) A/H3N2 cases. Of the CEBS, HEBS, IBS, and ISS systems deployed by the county to strengthen the early warning for respiratory diseases, CEBS detected a signal of unreported ARIs that facilitated further investigations and response.